Local fiscal distress and investment efficiency of local SOEs - Xinxin Liao; Yunguo Liu (China Journal of Accounting Research, 2014)
In this paper, we use A-share listed firms between 2002 and 2010 to investigate the relationship between local fiscal distress and the investment efficiency of local SOEs, along with the effect of corporate tax payments on this relationship. We find a positive relationship between the extent of local SOEs' overinvestment and the fiscal distress of the corresponding local government where the enterprise and this relationship become stronger for firms that pay fewer taxes. The pattern of underinvestment among local SOEs was in contrast, and these relationships do not exist for non-SOEs or central SOEs. Moreover, we find that expanding a firm's investment scale leads to an increase in total taxes paid, including income and turnover taxes, which further result in more local fiscal revenue. Overall, we conclude that local governments have an incentive to increase fiscal revenue when faced with fiscal distress by raising the investment scale of local SOEs and that the incentives and effects of such interventions appear to be stronger among firms that contribute less to local fiscal revenue.
Keywords: 650; Local government; Fiscal distress; Local state-owned enterprises; Overinvestment